Comprehensive Analysis Uncovers Prognostic and Immunogenic Characteristics of Cellular Senescence for Lung Adenocarcinoma - Lin, Weihao; Wang, Xin; Wang, Zhen; Shao, Fei; Yang, Yannan; Cao, Zheng; Feng, Xiaoli; Gao, Yibo; He, Jie (Frontiers in Cell and Developmental Biology, 2021)
Cellular senescence plays a crucial role in tumorigenesis, development and immune modulation in cancers. However, to date, a robust and reliable cellular senescence-related signature and its value in clinical outcomes and immunotherapy response remain unexplored in lung adenocarcinoma (LUAD) patients. Through exploring the expression profiles of 278 cellular senescence-related genes in 936 LUAD patients, a cellular senescence-related signature (SRS) was constructed and validated as an independent prognostic predictor for LUAD patients. Notably, patients with high SRS scores exhibited upregulation of senescence-associated secretory phenotype (SASP) and an immunosuppressive phenotype. Further analysis showed that SRS combined with immune checkpoint expression or TMB served as a good predictor for patients’ clinical outcomes, and patients with low SRS scores might benefit from immunotherapy. Collectively, our findings demonstrated that SRS involved in the regulation of the tumor immune microenvironment based on the SASP was a robust biomarker for the immunotherapeutic response and prognosis in LUAD.